Modification of Chroman Derivative Compounds and Their In Silico Antibacterial Activities - Jufrizal Syahri; Rahmiwati Hilma; Nurlaili Nurlaili (ALCHEMY Jurnal Penelitian Kimia, 2026)
This study reports the alkaline reflux synthesis of 6-chloro-4-chromanone (Ch) with the secondary amine dimethylamine (DA) to obtain chromanone-derived compounds with potential antibacterial activity. Spectroscopic analyses confirmed that 6-chloro-3-((dimethylamino)methyl)chroman-4-one (Ch-DA) was successfully formed in 46.37% yield and corresponded to the targeted structure. In silico antibacterial studies were performed to evaluate the interaction between the synthesized compound and the target protein (PDB ID: 3VOB). Molecular docking results indicated that Ch-DA exhibits antibacterial potential through the formation of hydrogen bonds with key amino acid residues at the active site. The standard ligand (9PC) showed a CDOCKER energy of-46.4867 kcal/mol with seven hydrogen bonds involving residues VAL310, ASN263, VAL207, ASN208, GLY205, LEU209, and GLY196. Meanwhile, Ch-DA demonstrated a CDOCKER energy of -34.3506 kcal/mol with three hydrogen bonds at GLY196, THR265, and ASP199. The positive control, chloramphenicol, produced a CDOCKER energy of -48.0224 kcal/mol and formed three hydrogen bonds with THR309, GLY205, and GLY196, whereas the precursor compound (Ch) showed lower activity (-27.546 kcal/mol) without hydrogen bond formation. These results indicate that the incorporation of a secondary amine group enhances antibacterial activity, with docking performance comparable to the positive control, suggesting that Ch-DA has potential as antibiotic drugs.